Pemanfaatan Sistem Informasi Manajemen untuk Meningkatkan Akurasi dan Kecepatan Pengambilan Keputusan di Lingkungan Bisnis Modern - Cindy Amelia; Muhammad Irwan Padli Nasution (Advances In Education Journal, 2025)
The rapid development of information technology has shifted the paradigm of modern organizational management. Management Information Systems (MIS) are now a crucial foundation for every organization, supporting fast and accurate decision-making. This study aims to analyze how the use of MIS can improve the accuracy and speed of decision-making in the modern business environment. The research method used is a qualitative descriptive approach with a literature study approach and case analysis of several companies in Indonesia, such as Gojek, Tokopedia, and Astra International. The results show that effective MIS utilization can accelerate information flow, improve data accuracy, and support strategic decision-making based on real-time data. Furthermore, human factors, organizational culture, and top management support play a crucial role in ensuring the success of MIS implementation. In conclusion, organizations that are able to optimally integrate MIS will be more adaptive, responsive, and competitive in today's digital era